Perceived Victimization in the Workplace: The Role of Situational Factors and Victim Characteristics - Aquino, Karl; Bradfield, Murray (Organization Science, 2000)
Harmful interpersonal behavior at work has generally been studied from the perspective of perpetrators. In contrast, theories of victimization suggest that other factors may also determine why certain individuals are more frequently harmed than others. For example, there may be situational factors that contribute to an environment that allows or fails to inhibit harmful actions. Other incidents of workplace harm may be consciously or unconsciously influenced by the victims themselves. This empirical study extends previous research on harmful workplace behavior by examining whether the situational variable of job status and the dispositional characteristics of aggressiveness and negative affectivity predict self-perceived victimization. Based on research in criminal victimology, we hypothesized that an employee's job status would be significantly related to perceived victimization. Research on victims of bullying was the basis for the predicted effects of negative affectivity and aggressiveness. Data were provided by a randomly selected sample of employees from a city government who completed a survey as part of an organizational assessment. We performed exploratory and confirmatory factor analyses on employee responses to develop suitable measures of victimization. The analyses revealed that perceived victimization took either direct (e.g., name-calling) or indirect (e.g., sabotaging work) forms. Hierarchical regression was used to test the study hypotheses. Results showed that job status did not significantly influence perceived victimization. However, employees who were high in aggressiveness and negative affectivity perceived higher levels of victimization than those who were low in these traits. Implications for organizations are discussed and future research directions are offered.